Molluscum contagiosum, inflamed molluscum and molluscum dermatitis in children. - Chiriac, A.; Brzezinski, P.; Chiriac, A.E.; Pinteala, T.; Foia, L. (European Journal of Pediatric Dermatology, 2015)
Molluscum contagiosum can be complicated by inflammation. The latter can be spontaneous and herald the regression of the infection. Moreover, the inflammation can be due to the treatment or be expression of a hypersensitivity reaction. Here are reported a case of inflamed molluscum contagiosum due to imiquimod and a case of eczematous molluscum dermatitis.